Using 3D laser scanning for estimating the capacity of corroded steel bridge girders: Experiments, computations and analytical solutions. (15th August 2022) - Tzortzinis, Georgios; Ai, Chengbo; Breña, Sergio F.; Gerasimidis, Simos
Abstract: This paper explores the use of three-dimensional (3D) laser scanning to evaluate deteriorated steel bridge girders due to corrosion. Initially, a naturally corroded beam from a decommissioned bridge in MA was scanned in the laboratory, and thickness contour maps were developed for mapping the remaining material of corroded parts. The contours are compared to thickness measurements obtained by ultrasonic thickness gauge, and the results validate the efficiency of 3D scanning as a potential technology for bridge inspections. Then, in a second phase, experimental testing of a corroded girder is performed to obtain the capacity and the mode of failure. Finally, in the last part of the paper, the 3D scanning data are combined through an automated procedure with finite element analysis and analytical provisions to examine whether 3D scanning can inform these two tools reasonably for accurate capacity predictions. The results provide good agreement between experimental and predicted failure loads, paving the way for a more efficient, safe, and time-saving inspection protocol. Highlights: 3D laser scanning of two naturally corroded girders is conducted. 2D thickness representations are proposed for corrosion mapping. Full scale experimental testing of a naturally corroded girder is performed. An automated procedure is developed to combine 3D scanning data and FEM. Post-processed 3D scanning data are combined with analytical procedures.